Correction to: Emerging Topics in the Behavioral Neuroscience of Tinnitus (10.1007/7854_2020_217) - Searchfield, Grant D.; Zhang, Jinsheng; Biswas, Roshni; De Ridder, Dirk; Deutsch, Brian; Hall, Deborah A.; Hébert, Sylvie; Kleinjung, Tobias; Kleinstäuber, Maria; Langguth, Berthold; Lopez-Escamez, Jose Antonio; Maslin, Michael R.D.; et al. (The Behavioral Neuroscience of Tinnitus, 2021)
Correction to: Chapter “Emerging Topics in the Behavioral Neuroscience of Tinnitus” in: Grant D. Searchfield et al., Curr Topics Behav Neurosci, https://doi.org/10.1007/7854_2020_217 The original version of this chapter unfortunately contained two errors: in author name and order of author. These two errors has been corrected and the below are the updated correction: 1. The author name “Sylvie Hall Hébert” is changed to “Sylvie Hébert”. 2. The order of author name Deborah A. Hall is listed before Sylvie Hébert.
CRIS-Team Scopus Importer:2024-03-27